The Potential of Endophite Fungus as Control of Bacterial Leaf Blight Disease in Rice - Syamsia, S (Jurnal Galung Tropika, 2023)
Endophytic fungi have the potential as biocontrol agents against bacterial leaf blight caused by a Xanthomonas oryzae pv Oryzae to support environmentally friendly agriculture. This study aims to select endophytic fungal isolates that have the potential as biocontrol agents against bacterial leaf blight. This research was divided into 3 stages: 1) isolation and rejuvenation of endophytic fungi isolate; 2) antagonistic test of endophytic fungi isolates against Xoo bacteria in vitro; 3) in vivo test of endophytic fungi isolates which are antagonistic in rice plants. As many as 16 isolates of endophytic fungi were isolated and rejuvenated, 6 isolates of endophytic fungi were antagonistic in vitro tests, the application of endophytic fungi isolates on rice plants was able to increase the resistance of rice plant highly susceptible, susceptible, moderately susceptible to moderately resistant, moderately susceptible and susceptible.